ДЕЛОПРОИЗВОДСТВО И АРХИВНОЕ ДЕЛО: РАЗВИТИЕ НАЦИОНАЛЬНОЙ ОТРАСЛЕВОЙ ТЕРМИНОЛОГИИ (НА МАТЕРИАЛЕ ТЕРМИНОЛОГИЧЕСКИХ СТАНДАРТОВ РОССИИ) - Kushneruk, Sergey Petrovich; Tyurikova, Nataliya Anatolyevna (Vestnik Volgogradskogo gosudarstvennogo universiteta. Serii͡a︡ 2, I͡A︡zykoznanie., 2013)
The article deals with the results of the statistic experiment aimed at presenting the main trends in terms of structural parameters changes for the units included in terminological standards. The branch of analyzed terms is office management and archive work. The interpretation of distribution parameters enable to reveal linguistic explication of logic-and-semantic development of examined branch via its terminology.